Effect of copper bhasma (an Ayurvedic preparation) supplementation on circulating lipids of chicks - CHOUDHARY, POOJA; CHADDA, ANKITA; KOCHAR, BHAWANI; SHARMA, D C (The Indian Journal of Animal Sciences, 2011)
The study was undertaken to assess the effect of copper bhasma supplementation in ration on the serum lipi4 fractions of chicks. One-month-old chicks (30) fed on commercial broiler ration were divided into control group (group C, n = 12) and experimental groups group E1, E2 and E3 (n=6). The ration ofgroup E1, E2 and E3 was supplemented with 1mg, 2 mg and 4 mg ofcopper bhasma, respectively, as pellets for 7 days, and control group was kept on regular ration without any supplementation. Blood from chicks ofboth groups was harvested on the eighth day after bleeding them to death, and serum lipid fractions along with the copper levels in whole blood, plasma and erythrocytes were estimated. The experimental groups showed significantly increased copper levels with simultaneous decrease in serum total lipids, phospholipids, trigylcerides, total cholesterol and increased HDL-cholesterol than the control group chicks. Thus, copper supplem ntation in chicks as copper bhasma decreased the serum lipid fractions except the HDL-cholesterol. Â